QUALITY PARAMETERS OF SUNFLOWER OIL AND PALM OLEIN DURING MULTIPLE FRYING - Paunović, Dragana M.; Demin, Mirjana A.; Petrović, Tanja S.; Marković, Jovana M.; Vujasinović, Vesna B.; Rabrenović, Biljana B. (Journal of Agricultural Sciences (Belgrade), 2020)
The refined sunflower and palm oil are used in the food industry for the production of fried potatoes. Literary data have been shown that the palm oil had less tendency to degradation than sunflower oil, due to its fatty acid composition. However, palm olein is a palm oil fraction and therefore has a different composition of fatty acids. The aim of this study was to investigate the quality of the refined palm olein in relation to the refined sunflower oil during the production of fried potatoes. The oil samples were used for multiple frying during the seven days (40 minutes per day at a temperature of 165oC). The peroxide value and free fatty acids content (acid value) was determined by standard analytical methods. The results showed that the peroxide value in sunflower oil and palm olein increased by 75.0% and 77.8%, while the acid value increased by 50.0% and 26.8%, respectively, in relation to their initial values in the fresh oil samples. Based on these results, it can be concluded that the palm olein was more suitable for frying. However, this finding can not be indicated with certainty because the quality of the oil depends on many more parameters, not only of analyzed in this paper.